Evaluation of Lip Prints on Different Supports Using a Batch Image Processing Algorithm and Image Superimposition - Herrera, Lara Maria [UNESP]; Fernandes, Clemente Maia da Silva [UNESP]; Serra, Mônica da Costa [UNESP] (Wiley, 2018)
This study aimed to develop and to assess an algorithm to facilitate lip print visualization, and to digitally analyze lip prints on different supports, by superimposition. It also aimed to classify lip prints according to sex. A batch image processing algorithm was developed, which facilitated the identification and extraction of information about lip grooves. However, it performed better for lip print images with a uniform background. Paper and glass slab allowed more correct identifications than glass and the both sides of compact disks. There was no significant difference between the type of support and the amount of matching structures located in the middle area of the lower lip. There was no evidence of association between types of lip grooves and sex. Lip groove patterns of type III and type I were the most common for both sexes. The development of systems for lip print analysis is necessary, mainly concerning digital methods.
Keywords: cheiloscopy; forensic dentistry; forensic science; human identification; investigative technique; lip print